2017
DOI: 10.1136/bmjopen-2016-013281
|View full text |Cite
|
Sign up to set email alerts
|

Postural sway, working years and BMI in healthy truck drivers: an observational study

Abstract: ObjectivesThe following study analyses the influence of risk factors among the occupational group of truck drivers on postural control and body mass index (BMI).DesignObservational study.SettingOne motorway station close to several highways in Germany.Participants180 truck drivers (177 male/3 female), aged 21–65 years old, took part in this study.Outcome measuresPostural control was examined using a pressure plate. In order to examine the influence of body weight (BMI) and working years on postural control, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 24 publications
4
4
0
5
Order By: Relevance
“…The study showed an association between years of driving experience and overweight/obesity. This finding was consistent with previously conducted studies in other areas [ 14 , 26 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The study showed an association between years of driving experience and overweight/obesity. This finding was consistent with previously conducted studies in other areas [ 14 , 26 ].…”
Section: Discussionsupporting
confidence: 94%
“…Studies conducted worldwide regarding the prevalence of abnormal BMI revealed that 40% in Manipal, India [ 21 ], 55.5% in Chennai, India [ 11 ], 64% in central North Carolina, USA [ 16 ], 69% in South Africa [ 22 ], 71% in India [ 23 ], 75.2% in Mexico [ 8 ], 76% in Germany [ 24 ], 79.2% in Brazil [ 18 ], 91.1% in Arkansas, USA [ 9 ], and 93.3% in the USA [ 25 ]. The factors that contribute to overweight and obesity are varied and might include age, income, educational status, nutrition, sleep duration, physical exercise, daily working hours, and years of driving experience [ 1 , 3 , 7 , 12 , 14 – 16 , 26 – 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their limited access to food, specifically balanced food choices, and their isolated and small work place are just two examples of the challenging work setting. This survey confirmed the results of other studies regarding an above average BMI in the truck driver population [7,22] and a high prevalence of bad health conditions such as back pain or other [9,23]. European truck drivers driving through Germany appear to be affected by their difficult working conditions in similar ways than drivers in other European countries, the U.S., or Australia [9,17,[23][24][25].…”
Section: Discussionsupporting
confidence: 88%
“…While the need for truck drivers is increasing, the working conditions have only slightly improved over the years. Truck drivers often report sleep problems and back pain as well as other physical health problems [5][6][7]. Behavioural health problems include alcohol abuse, anxiety, depression, job strain, fatigue, and social isolation [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Findings in this review are complemented by a recent smaller review reporting a high prevalence of LBP and neck pain among bus drivers. 28 With a much larger pooled sample (N = 18 882), the current review reports a meta-prevalence of LBP (53%), consistent with the high prevalence of LBP reported in other recent professional driving studies [29][30][31] at 61.7%, 49%, and 54% respectively. Another systematic review of the global prevalence of LBP reported a mean 12-month prevalence of 38.9%.…”
Section: Prevalence Of Lbpsupporting
confidence: 88%